Developing Thinking Reading Classrooms: Insight from Pre-Service EFL Teachers’ Lesson Plans and Classroom Instructions - Dwi Puji Hastuti; Diah Kristina; Endang Setyaningsih (IAIN Salatiga, 2022)
Numerous studies have investigated the integration of critical thinking in EFL classrooms and textbooks. Still, relatively few have investigated the integration of critical thinking into reading lesson plans and classroom instructions. The current study adopted a qualitative case study approach to provide insight into how pre-service EFL teachers infused critical thinking skills into online reading classrooms. The study also gives information on pre-service EFL teachers' challenges in critical thinking integration into reading classrooms. Eight pre-service EFL teachers who completed all three phases of the faculty-mandated teaching practicum program participated in the study. Document analysis, virtual classroom observations, and semi-structured interviews were used as data collection techniques to fulfill the research objectives. As the study framework, Bloom's revised taxonomy was applied to lesson plan data to examine how critical thinking components are incorporated. Virtual classroom observations illuminated the incorporation of critical thinking into reading lessons. In addition, semi-structured interviews were conducted to gather more information regarding the challenges of integrating critical thinking skills. The present study reveals that pre-service EFL teachers integrated critical thinking aspects into reading online classes with a greater emphasis on lower-order cognitive than higher-order cognitive processes. It implies that pre-service EFL teachers had insufficient preparation for teaching practicum programs. Due to the significance of critical thinking skills for EFL students, this study recommends that teacher training institutes strengthen the critical thinking abilities of pre-service EFL teachers so that they are more equipped to teach and promote critical thinking in EFL classrooms.Keywords: classroom instructions, critical thinking, lesson plans, pre-service teachers